Recursos de Investigación en ciencias de la salud: Métodos de trabajo en bioinformática y genética aplicados al estudio del vector de la Enfermedad de Chagas - Rincón Galvis, Helen Jineth (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2022)
In order to obtain knowledge about techniques here It refers to a two examples of the use of task-working in bioinformatics, and obtain two possible outcomes based on a research workshop guided by professor; Aims were using applied biological sciences to solve public health problems. The use of them and the importance of their application are mentioned.